2017
DOI: 10.1515/pielxxiw-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of cervical cancer prevention

Abstract: cOrrespOnding AuthOr/AutOr dO kOrespOndencji:Andrea Obročníková Faculty of health care in prešov, university of prešov ul. partizánska 1, 080 01 prešov, slovak republic tel. +421 51 756 24 60 e-mail: andrea.obrocnikova@unipo.sk StreSzczenieWiedza, poStaWy i praKtyKa W profilaKtyce raKa SzyjKi macicy Wprowadzenie. Rak szyjki macicy jest najbardziej powszechnym nowotworem narządów płciowych oraz jednym z wiodących przyczyn zgonów wśród kobiet w Słowacji. Obecnie tak umiejscowionemu nowotworowi można zapobiec jeś… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The majority of participants in this study also indicated vaginal bleeding, pelvic pain, and pain during sexual intercourse as signs and symptoms of cervical cancer, while a few indicated vaginal discharges and odours. This is consistent with [7] and [22] findings that identified vaginal discharges, painful sex, and excessive bleeding as cervical cancer manifestations. However, the present study's findings on signs and symptoms contradict those of [23], who found that the majority of young female students were unaware of any signs or symptoms of cervical cancer, and [24] who found that participants lacked adequate knowledge about cervical cancer signs and symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of participants in this study also indicated vaginal bleeding, pelvic pain, and pain during sexual intercourse as signs and symptoms of cervical cancer, while a few indicated vaginal discharges and odours. This is consistent with [7] and [22] findings that identified vaginal discharges, painful sex, and excessive bleeding as cervical cancer manifestations. However, the present study's findings on signs and symptoms contradict those of [23], who found that the majority of young female students were unaware of any signs or symptoms of cervical cancer, and [24] who found that participants lacked adequate knowledge about cervical cancer signs and symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing data from similar studies regarding women's knowledge about vaccination in Slovakia and Latvia results were similar -33% vs. 31%, respectively. 8 Whereas knowledge about cytology testing were higher in other countries, for example, 83% of women in Slovakia and 77% in Italy knew that cytology testing is one of the prevention methods for cervical cancer. 8,11 Cytology is still the cornerstone of diagnostic of cervical precancerous changes, although more and more different approaches such as HPV testing are introduced in the screening programmes.…”
Section: Discussionmentioning
confidence: 99%
“…8 Whereas knowledge about cytology testing were higher in other countries, for example, 83% of women in Slovakia and 77% in Italy knew that cytology testing is one of the prevention methods for cervical cancer. 8,11 Cytology is still the cornerstone of diagnostic of cervical precancerous changes, although more and more different approaches such as HPV testing are introduced in the screening programmes. 12 It is worth to note, that almost half of respondents of the current study considered that cervical precancerous changes is malignant disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation